Beyond the seizures: Ketogenic Diets in the battle against drug-resistant epilepsy - Domańska, Natalia; Bojarska, Małgorzata; Bogucka, Julia; Brzyska, Anna; Kosowska, Michalina; Piecewicz-Szczęsna, Halina (Journal of Education, Health and Sport, 2025)
Introduction: Epilepsy is a chronic, non-infectious and one of the most common neurological disease. About 70 million people worldwide suffer from it and these are patients of all ages. Despite the existence of many anticonvulsants and multiple lines of treatment, some patients still experience symptoms of the epilepsy. International league against epilepsy says that one-third of people with epilepsy fail to control it with anti-epileptic drugs (AED) and continue to have seizures. Purpose: The aim of the study is to analyze the impact of using a ketogenic diet in patients with epilepsy that meets the criteria for drug-resistant epilepsy. Materials and method: In April 2024, articles found in the Medline (Pubmed) databases were selected by using the following keywords: ketogenic diet in drug-resistant epilepsy, drug-resistant epilepsy, ketogenic diet and selected articles from 2018-2023. Conclusions: In the ketogenic diet, ketones formed from the oxidation of fatty acids are the source of energy instead of glucose. Ketones increase the amount of inhibitory neurotransmitters and glutathione. It improves neuronal hemostasis and increases cells’ resistance during excessive electrical discharges in the brain. These qualities are responsible for the antiepileptic profile of the ketogenic diet. Patients who follow a ketogenic diet experience fewer seizures attacks. We do not know the long-term side effects of the ketogenic diet yet and it is impossible to make a definitive thesis. Scientists are working to prove the validity of ketogenic diet in drug-resistant epilepsy.